Civic Virtue in the Deliberative System - Daniel Hutton Ferris (Journal of Deliberative Democracy)
The normative stability of a deliberative and democratic political order and the creativity and quality of the decisions its produces depend on citizens developing civic orientations and capacities through participation in deliberative events aiming at the cooperative solution of political problems. That, at least, is the claim made by critics of the systems approach to deliberative democracy, who argue that its proponents have lost sight of the educative function that respectful public reasoning plays for citizens. In this article I offer a response to this line of argument. There is no good philosophical reason to suppose that only unitary deliberation can perform an educative function for citizens. The kinds of informal and uncooperative public speech that occur in distributed deliberative processes can also develop participants’ civic capacities and civic virtue – and not merely through their systemic effects. This is an insight that should encourage us to rethink the design and facilitation of deliberative forums and pay more attention to citizens’ everyday deliberation.